Facebook como herramienta de comunicación ambiental: estudio comparativo en GADS provinciales Ecuador 2023 - Morocho Cusme, Evelyn Mayerly; Jaramillo Ayala, Génesis Nahomi (Machala, 2024)
The work is an analysis of the environmental content publications on Facebook of public organizations, whose function established in the Constitution of the Republic of Ecuador is to manage the environmental resources of their territories, such as the Provincial Decentralized Autonomous Governments. The research objectives are to determine the potential and limitations of the promotion of environmental management in public organizations, through a comparative analysis on three Facebook platforms of provincial GAD's of Ecuador, year 2023. For this purpose, the characterization of digital platforms and social networks in the three public institutions, through mapping, evaluate the environmental publications of the three institutions, through a content analysis, with the use of Artificial Intelligence and determine similarities and differences in content publications environmental on Facebook of the three organizations, through a comparative analysis. To carry out this descriptive research, mixed methodology was used: qualitative and quantitative with the application of techniques such as: descriptive mapping, content analysis technique, use of AI, comparative analysis technique and interviews with experts. The environmental content publications that each GAD makes are informative, they are few and limited, they include flora and fauna, but the format of each GAD varies
El trabajo es un análisis de las publicaciones de contenido ambiental en Facebook de las organizaciones públicas, cuya función establecida en la Constitución de la República del Ecuador es gestionar los recursos ambientales de sus territorios, como Gobiernos Autónomos Descentralizados Provinciales. Se plantea como objetivo de investigación determinar las potencialidades y limitaciones de la promoción de la gestión ambiental en las organizaciones públicas, a través de un análisis comparativo en tres plataformas de Facebook de GAD's provinciales de Ecuador, año 2023. Para ello se caracterizaron plataformas digitales y redes sociales en las tres instituciones públicas, mediante un mapeo, evaluación de las publicaciones ambientales, mediante un análisis de contenido, uso de la Inteligencia Artificial y semejanzas y diferencias en publicaciones de contenido ambiental en Facebook de las tres organizaciones, mediante un análisis comparativo. Para llevar a cabo dicha investigación de tipo descriptivo, se empleó la metodología mixta: cualitativa y cuantitativa con la aplicación de técnicas como: mapeo descriptivo, técnica de análisis de contenido, uso de IA, técnica de análisis comparativo y entrevistas a expertos. Las publicaciones de contenido ambiental que cada GAD realizó en los meses de mayo, junio y julio del 2023 fueron solo informativas, escasas y limitadas, incluyen flora y fauna, pero el formato de cada GAD varía.
Keywords: COMUNICACION AMBIENTAL; RED SOCIAL; USO DE FACEBOOK; GAD PROVINCIAL